Caracterización geográfica de la familia Thripidae en ornamentales de exportación en la provincia de Cotopaxi - Gómez Calvopiña, Pablo Patricio (2020)
In Cotopaxi province, the thrips species belonging to the Thripidae family have not been identified in ornamental crops for export, which is essential since ornamentals constitute a significant income source for the country due to their exports. On the other hand, some species of thrips are considered quarantine pests in different countries. Some species of thrips intercepted in ornamental crops for export are recorded. Four species were found: Frankliniella auripes, Frankliniella panamensis, Frankliniella occidentalis, Thrips tabaci, where Frankliniella occidentalis is the one with the highest number of interceptions in ornamental crops, in Latacunga canton, in the ornamental species Rosa sp.